Implementation of Health Belief Model on Knowledge of Hypertension Prevention among At-Risk Adolescents in Bojongsawah Village, Kebon Pedes Subdistrict, District - Rita Siti Hawa; Irawan Danismaya; Amir Hamzah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Hypertension is one of the global health problems whose prevalence continues to increase, including in adolescents. Lack of knowledge about the risk factors, prevention, and impact of hypertension can exacerbate long-term health risks. This study aims to analyze the effect of Health Belief Model (HBM) implementation on increasing the knowledge of at-risk adolescents about hypertension prevention. This study used a quasi-experimental design with a One Group Pre-Test and Post-Test approach. The research sample was 40 at-risk adolescents in Bojong Sawah Village, who were selected using convenience sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability. Data were analyzed univariately and bivariately using the Paired Sample T-Test test. The results showed that there was a significant increase in the level of knowledge of adolescents after the implementation of HBM (mean pre-test: 17.00; post-test: 24.00). The statistical test showed a p value = 0.000 (<0.05), which indicated that the implementation of HBM had a significant effect on increasing respondents' knowledge. In conclusion, the implementation of HBM is effective in increasing adolescents' knowledge about hypertension prevention. This study recommends the application of HBM in health education programs to address hypertension, especially in the adolescent age group.